Addition of Calcium Carbonate (CaCO3) and Magnesium Sulfate (MgSO4) to Vannamei Shrimp (Litopenaeus vannamei) Rearing Media in Fresh Water - Andre Rachmat Scabra; Muhammad Marzuki; Muhammad Rifki Alhijrah (Jurnal Biologi Tropis, 2023)
Vannamei shrimp cultivation in freshwater media is still not optimal. Scabra et al., 2022 stated that the growth of vannamei shrimp reared on media supplemented with CaCO3 was higher than that reared on media without the addition of CaCO. However, it is still lower than the vannamei shrimp reared in seawater media. The addition of other types of minerals is needed to complement CaCO3 in supporting growth. The purpose of this study was to determine the effect of rearing vaname shrimp on low-salinity media with the addition of CaCO3 and MgSO4 ratios with different doses. The treatment in the study was the addition of CaCO3 : MgSO4 with different ratios, namely 40:0 (P2), 40:20 (P3), 40:40 (P4), and 40:60 (P5). A treatment was also applied which was a positive control, namely the rearing of vannamei shrimp in seawater media (P1). The results showed that the best specific growth values were P1 (3.83%), P4 (3.64%), P5 (3.5%), P3 (3.46%), and P2 (3.42%) ). In fresh water rearing, P4 was the best treatment which resulted in a survival rate of 77%, a specific weight growth rate of 3.64%, and a specific length growth rate of 2.14%. Shrimp growth in fresh water media is still not as high as maintenance in seawater media. Therefore, it is still necessary to add other types of minerals that can support growth.